Redução da população de Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) com manejo comportamental na cultura da soja - Kruger, Alexandra P.; Ramos, Rodrigo S.; Favoreto, Ana L.; Favetti, Bruna M.; Tran, Khai; Broms, Kristin; Andrade, Thais; Galvan, Tederson (BioAssay, 2025)
Spodoptera frugiperda (J.E. Smith, 1797) (Lepidoptera: Noctuidae), also known as fall armyworm, is one of the main pests in corn and is becoming increasingly frequent in soybean. Due to its polyphagous nature, it adapts rapidly to host plants, and the alternation between soybean and corn favors its development and permanence in agricultural environments. The damage caused to soybeans varies according to the larval instars, feeding on seedlings, leaves, shoots, flowers, and pods. The increasing incidence of S. frugiperda in soybean crops and the challenges for its control, including insecticide resistance and genetically modified plants, highlight the urgent need for continuous monitoring and research to develop sustainable and integrated management methods. In this context, the objective of this work was to test the application of the synthetic sex pheromone Pherogen® Spray FAW, which aims to suppress the mating of S. frugiperda through mating disruption. Pherogen® Spray FAW was responsible for reducing the capture of male S. frugiperda moths and reducing the population of this species in commercial Bt soybean crops in three different Brazilian states. These results suggest that the use of behavioral management, through mating disruption with pheromones, is a control alternative, as there is greater difficulty for males to find females and mate, consequently, reducing the population of caterpillars.